Political Communication of The General Election Commission and The Election Supervisory Board in Responding to Allegations of Voter Data Leakage - Yusuf Samad, M.; Setiono, Sigit; Ayu Permatasari, Diah; Pribadi, Kukuh; Dahlian Persadha, Pratama (International Journal of Advanced Multidisciplinary, 2024)
The alleged case of voter data leakage in the General Election Commission's (KPU) Sidalih application occurred ahead of the 2024 elections, the voter data was allegedly traded on BreachForums by an anonymous account. Responding to the alleged case, the political communication of the KPU and the Election Supervisory Board (Bawaslu) through the Twitter (X) social media account is very minimal, even the KPU did not convey its attitude at all on its Twitter social media account. This study aims to determine how the KPU RI and Bawaslu RI utilize Twitter (X) social media as a strategic communication tool and how to utilize Twitter (X) social media in responding to the alleged leakage of KPU's data. The research method used is a qualitative research method with a case study. The results showed that the lack of information about the alleged leakage of KPU data conveyed by KPU RI and Bawaslu RI through their Twitter social media channels, this was also exacerbated by the absence of dialogic communication on uploads related to the alleged leakage. The suggestion of this research is that KPU RI and Bawaslu RI need to optimize their political communication through Twitter social media management by consistently providing the latest information related to the alleged leakage of KPU data as well as building dialogical communication with the public or netizens. In addition, it is also necessary to improve the security infrastructure of the Sidalih application.